Hydrogel wear-resistant coating for PEEK artificial joint and preparation method
By preparing hydrogel coating on PEEK materials, using the combination of acrylamide and other components and kappa carrageenan, the problem of poor friction and wear performance in body fluids is solved, and the friction coefficient and wear rate are reduced, and the biological is improved. Compatibility and mechanical properties promote their application as bone implant material.
Patent Information
- Application Number
- CN202411417799.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-07
AI Technical Summary
The friction coefficient of PEEK material is high when lubricated in body fluids, resulting in large wear, limiting its clinical application in bone tissue replacement surgery.
The preparation method of hydrogel wear-resistant coating is adopted, and acrylamide, N,N'-methylene bisacrylamide, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenyl acetone, etc. The combination of ingredients with κ carrageenan and potassium chloride forms a hydrogel precursor solution, which is combined with the PEEK surface after ultrasonic treatment to form a high-performance coating.
The friction coefficient and wear rate of PEEK materials are significantly reduced, the wetting and mechanical properties of the surface are improved, and the adaptability to bone implant materials is enhanced.
Smart Images

Figure CN119258274A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a wear-reducing and wear-resistant coating material, in particular to a hydrogel wear-resistant coating for PEEK artificial joints and a preparation method thereof, which is mainly used as a surface coating for replacing and repairing PEEK materials for artificial joints, and belongs to the field of composite materials and biomedical material technology. Background Art
[0002] In bone tissue replacement surgery, metal materials and ceramic materials are commonly used bone replacement materials. However, their mechanical properties do not match those of bone tissue, resulting in stress shielding after implantation, leading to injuries such as osteolysis and secondary fractures. Polyetheretherketone (PEEK) is an artificial synthetic plastic material with similar mechanical properties to bone tissue and excellent biocompatibility. It can be prepared into bone shapes through 3D printing and is currently the most promising bone tissue replacement material. However, PEEK has poor surface wettability, a high friction coefficient under body fluid lubrication, and a large amount of wear, which can easily lead to inflammation at the implant site, severely limiting its clinical application. Therefore, how to improve the friction and wear properties of PEEK is an urgent problem to be solved. Summary of the invention
[0003] In order to overcome the problem of poor friction and wear performance of PEEK in the prior art, the purpose of the present invention is to provide a hydrogel wear-resistant coating for PEEK artificial joints and a preparation method thereof, wherein the hydrogel wear-resistant coating has good friction and wear performance and biocompatibility.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing a hydrogel wear-resistant coating for a PEEK artificial joint comprises the following steps:
[0006] (1) dissolving acrylamide, N,N'-methylenebisacrylamide and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone in deionized water and stirring until dissolved, or dissolving acrylamide, N,N'-methylenebisacrylamide and ammonium persulfate in deionized water and stirring until dissolved; adding kappa carrageenan and potassium chloride under heating, and sonicating to form a hydrogel precursor solution;
[0007] (2) Precooling the PEEK and immersing it in a hydrogel precursor solution to form a hydrogel coating, which is then cured to obtain a hydrogel wear-resistant coating for a PEEK artificial joint.
[0008] Furthermore, in the hydrogel precursor solution, the concentration of acrylamide is 100-800 mg / mL, the concentration of N,N'-methylenebisacrylamide is 0.1-20 mg / mL, and the concentration of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone is 0.05-20 mg / mL.
[0009] Furthermore, the concentration of κ carrageenan is 12 to 30 mg / mL, the concentration of potassium chloride is 1.2 to 30 mg / mL, and the concentration of ammonium persulfate is 0.01 to 10 mg / mL.
[0010] Furthermore, the heating temperature is 60-90°C.
[0011] Furthermore, the ultrasonic power is 30W, and the ultrasonic time is 0.5min to 3min.
[0012] Furthermore, the precooling temperature is -18°C to -4°C, and the time for immersing the precooled PEEK in the hydrogel precursor solution is 0.5s to 10s.
[0013] Furthermore, the thickness of the hydrogel coating is 200 to 1800 μm.
[0014] Furthermore, when the hydrogel precursor solution contains 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, the curing conditions are: -1 、UV power is 350mW / cm 2 UV curing for 50min to 90min;
[0015] When the hydrogel precursor solution contains ammonium persulfate, the curing conditions are: heating at 70 to 90° C. for 60 to 120 minutes.
[0016] Furthermore, the method further comprises the following steps:
[0017] (3) repeating step (1) to obtain a hydrogel precursor solution;
[0018] (4) adding the hydrogel precursor solution obtained in step (3) dropwise onto the hydrogel wear-resistant coating for PEEK artificial joints prepared in step (2), and curing the solution to obtain a double-layer hydrogel wear-resistant coating for PEEK artificial joints.
[0019] A hydrogel wear-resistant coating for PEEK artificial joints prepared according to the method described above.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] In the present invention, the acrylamide monomers free in the solution and the C=O structure in PEEK are disconnected after ultraviolet irradiation, and a grafting process triggered by ultraviolet irradiation occurs. Under the action of the crosslinking agent MBAA, the remaining monomers in the solution undergo a polymerization reaction with the acrylamide grafted onto PEEK to form a hydrogel network, namely polyacrylamide PAAm. The reaction formula is as follows:
[0022]
[0023] During the polymerization process, PAAm can react with PEEK to form covalent crosslinks, thereby increasing the bonding force between PEEK and the coating. Using a higher concentration of PAAm can increase the entanglement between the molecular chains, making the surface hydration layer thicker and providing sufficient lubrication, thereby reducing friction. The addition of KC (κ carrageenan) can improve the mechanical properties of the coating, while also improving the surface wetting properties, making it easier for water to spread on the surface and act as a lubricant. The colloid formed by KC is more conducive to the molding of the coating on the curved surface, which can effectively promote the development of PEEK materials as bone implant materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the infrared spectrum of the hydrogel coating;
[0025] Figure 2 The surface morphology of the coating after swelling; (a) is the three-dimensional morphology of the coating, and (b) is the three-dimensional morphology contour curve;
[0026] Figure 3 The tribological performance diagram of coatings with different thicknesses;
[0027] Figure 4 The long-term friction and wear performance diagram of the hydrogel coating; among them, (a) is the friction coefficient curve of 28,800 times, (b) is the wear morphology, (c) is the three-dimensional contour of the wear morphology, and (d) is the wear morphology contour curve.
[0028] Figure 5 Biocompatibility of the hydrogel coating. DETAILED DESCRIPTION
[0029] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0030] Since hydrogel is a type of material with extremely high water content, the thick hydration layer on the surface can act as a lubricant, reduce friction and thus reduce wear. At the same time, its internal three-dimensional network structure is suitable for cell growth, making it a high-quality material for solving the problem of friction and wear on the PEEK surface. Therefore, the present invention designs a hydrogel coating with high bonding strength with PEEK and low friction properties, realizes its coating preparation process on complex curved surfaces, and can effectively promote the development of PEEK materials as bone implant materials.
[0031] A method for preparing a hydrogel wear-resistant coating for a PEEK artificial joint of the present invention comprises the following steps:
[0032] (1) First, acrylamide (AAm), N,N'-methylenebisacrylamide (MBAA) and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (Irgacure 2959) are dissolved in deionized water and stirred until fully dissolved, heated in a water bath and κ carrageenan and potassium chloride are added thereto (the water bath heating temperature is 60-90°C), and the bubbles and dissolved gases in the solution are removed by ultrasound (ultrasonic crusher, ultrasonic power 30W, ultrasonic time 0.5min-3min), to form a hydrogel precursor solution. In the hydrogel precursor solution, the concentration of AAm is 100-800 mg / mL, the concentration of MBAA is 0.1-20 mg / mL, the concentration of Irgacure 2959 is 0.05-20 mg / mL, the concentration of κ carrageenan is 12-30 mg / mL, and the concentration of potassium chloride is 1.2-30 mg / mL.
[0033] (2) PEEK was precooled at -18°C to -4°C, and quickly immersed in the hydrogel precursor solution for 0.5s to 10s. A hydrogel coating with a thickness of 200 to 1800 μm was taken out, and the surface of the hydrogel coating was covered with a PTFE film and placed in a UV box for curing (UV wavelength of 365 nm). -1 , UV power is 350mW / cm 2 The ultraviolet curing time is 50 minutes to 90 minutes), so that the hydrogel precursor solution and PEEK react, cross-link and self-assemble to form a supramolecular hydrogel, and obtain a hydrogel wear-resistant coating for PEEK artificial joints.
[0034] The present invention may also include the following steps:
[0035] (3) Repeat step (1) to obtain a hydrogel precursor solution, add the hydrogel precursor solution dropwise to the hydrogel wear-resistant coating for PEEK artificial joints prepared in step (2), cover the surface with a glass sheet and place in a UV box for curing (UV wavelength is 365 nm) -1 , UV power is 350mW / cm 2 The UV curing time is 1 h), and photosensitive polymerization is performed to obtain a double-layer hydrogel wear-resistant coating for PEEK artificial joints.
[0036] The method of the invention can prepare three or more layers of hydrogel wear-resistant coatings for PEEK artificial joints.
[0037] In the preparation method of the hydrogel wear-resistant coating for PEEK artificial joints of the present invention, Irgacure2959 can be replaced by ammonium persulfate (APS), the concentration of APS is 0.01-10 mg / mL, UV curing is replaced by water bath heating curing (heating polymerization), the water bath heating temperature is 70-90°C, the water bath time is 60min-120min, and the rest remains unchanged.
[0038] The reaction between the hydrogel precursor solution and PEEK in the present invention is:
[0039] Example 1: Preparation of hydrogel wear-resistant coating for PEEK artificial joints
[0040] (1) 5 g of acrylamide, 0.005 g of N,N'-methylenebisacrylamide and 0.005 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone were dissolved in 10 ml of deionized water and stirred to form a solution 1;
[0041] (2) heating solution 1 to 80° C. in a water bath, adding 0.2 g of κ carrageenan and 0.02 g of potassium chloride thereto, and removing bubbles and dissolved gases in the solution by ultrasonication (ultrasonicator, ultrasonic power of 30 W, ultrasonic time of 1 min) to form a hydrogel precursor solution;
[0042] (3) The artificial joint made of PEEK was precooled to -18°C, immersed in the hydrogel precursor solution for 1 second and taken out to form a hydrogel coating with a thickness of 200 μm. The surface was covered with a PTFE film and placed in a UV box for curing (UV wavelength of 365 nm). -1 , UV power is 350mW / cm 2 The UV curing time is 1h), so that the hydrogel precursor solution reacts with PEEK to crosslink and self-assemble to form a supramolecular hydrogel, and a hydrogel wear-resistant coating for PEEK artificial joints is obtained. The average friction coefficient of the coating material is 0.02, and the wear rate is 4.5×10 -5 mm 3 / Nm.
[0043] The synthesized hydrogel coating was analyzed by infrared spectroscopy. The infrared spectrometer used was Nicolet iS50. Figure 1 Shown: 841cm -1 , 919cm -1 Represents two polysaccharide groups on kappa carrageenan, 3300 cm -1 The broad peaks represent the hydroxyl groups on the sugar. The coating masks the infrared absorption peak of PEEK and does not show the special groups on the surface of PEEK.
[0044] The synthetic hydrogel coating was subjected to a bonding test using a peeling tensile test, and the cross-sectional bonding strength was found to be 288 Jm -2 The material mechanical properties test shows that the elastic modulus is 977KPa, and the cyclic compression test proves the durability of the material, which meets the use requirements of the coating. Figure 2 (a) and (b) show the morphology of the hydrogel coating surface after swelling. Due to the covalent cross-linking of the hydrogel and PEEK, the swelling of one side is restricted, and it can only swell toward the other side and squeeze each other to form a textured surface. This type of textured surface is similar to real cartilage, not completely flat, and is also one of the factors that can enhance fluid lubrication and reduce friction.
[0045] Example 2
[0046] (1) dissolving 6 g of acrylamide, 0.006 g of N,N'-methylenebisacrylamide and 0.005 g of ammonium persulfate in 10 ml of deionized water and stirring to form solution 2;
[0047] (2) heating solution 2 to 80° C. in a water bath, adding 0.3 g of κ carrageenan and 0.03 g of potassium chloride thereto, and removing bubbles and dissolved gases in the solution by ultrasonication (ultrasonic crusher, ultrasonic power of 30 W, ultrasonic time of 1 min) to form a hydrogel precursor solution;
[0048] (3) The PEEK sheet was precooled to -18°C, a hydrogel precursor solution was dripped onto the surface, the surface was covered with a glass sheet and placed in an 80°C water bath for 1.5 h to allow the hydrogel precursor solution to react with PEEK to crosslink and self-assemble to form a supramolecular hydrogel, thereby obtaining a hydrogel wear-resistant coating for PEEK artificial joints. The average friction coefficient of the coating material was 0.02, and the wear rate was 1.77×10 -5 mm 3 / Nm.
[0049] It can be seen from Examples 1 and 2 that the protrusions of the present invention can be prepared on a curved surface or on a flat surface.
[0050] Example 3
[0051] (1) 6 g of acrylamide, 0.006 g of N,N'-methylenebisacrylamide and 0.006 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone were dissolved in 10 ml of deionized water and stirred to form a solution 3;
[0052] (2) heating solution 3 to 80° C. in a water bath, adding 0.3 g of κ carrageenan and 0.03 g of potassium chloride thereto, and removing bubbles and dissolved gases in the solution by ultrasonication (ultrasonicator, ultrasonic power of 30 W, ultrasonic time of 1 min), to form a hydrogel precursor solution 1;
[0053] (3) Precool the PEEK sheet to -18°C, drip the hydrogel precursor solution 1 onto the surface, cover the surface with a glass sheet and place in a UV box for curing (UV wavelength is 365 nm) -1 , UV power is 350mW / cm 2 UV curing time is 1 h), to obtain a hydrogel coating 1;
[0054] (4) dissolving 2 g of acrylamide, 0.002 g of N,N'-methylenebisacrylamide and 0.002 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone in 10 ml of deionized water and stirring the mixture to form a solution 4;
[0055] (5) heating solution 4 to 80° C. in a water bath, adding 0.12 g of κ carrageenan and 0.012 g of potassium chloride thereto, and removing bubbles and dissolved gases in the solution by ultrasonication (ultrasonic crusher, ultrasonic power 30 W, ultrasonic time 0.5 min), to form a hydrogel precursor solution 2;
[0056] (6) Add the hydrogel precursor solution 2 dropwise onto the hydrogel coating 1, cover the surface with a glass sheet and place in a UV box for curing (UV wavelength is 365 nm). -1 , UV power is 350mW / cm 2 The UV curing time was 1 h) to obtain a double-layer hydrogel coating. The friction coefficient of the multi-layer hydrogel coating was 0.016 and the wear rate was 1.06×10 -5 mm 3 / Nm.
[0057] Example 4
[0058] Same as Example 1, except that the thickness of the hydrogel coating is 600 μm.
[0059] Example 5
[0060] Same as Example 1, except that the thickness of the hydrogel coating is 1000 μm.
[0061] Example 6
[0062] Same as Example 1, except that the thickness of the hydrogel coating is 1400 μm.
[0063] Example 7
[0064] Same as Example 1, except that the thickness of the hydrogel coating is 1800 μm.
[0065] Example 8
[0066] (1) dissolving 1 g of acrylamide, 0.001 g of N,N'-methylenebisacrylamide and 0.2 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone in 10 ml of deionized water and stirring the mixture to form a solution 1;
[0067] (2) heating solution 1 to 60° C. in a water bath, adding 0.12 g of κ carrageenan and 0.012 g of potassium chloride thereto, and removing bubbles and dissolved gases in the solution by ultrasonication (ultrasonicator, ultrasonic power 30 W, ultrasonic time 0.5 min), to form a hydrogel precursor solution;
[0068] (3) The artificial joint made of PEEK was precooled to -13°C, immersed in the hydrogel precursor solution for 1 second and taken out to form a hydrogel coating with a thickness of 200 μm. The surface was covered with a PTFE film and placed in a UV box for curing (UV wavelength of 365 nm). -1 , UV power is 350mW / cm 2 The ultraviolet curing time is 50 minutes), so that the hydrogel precursor solution and PEEK react, cross-link and self-assemble to form a supramolecular hydrogel, thereby obtaining a hydrogel wear-resistant coating for PEEK artificial joints.
[0069] Example 9
[0070] (1) 8 g of acrylamide, 0.2 g of N,N'-methylenebisacrylamide and 0.1 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone were dissolved in 10 ml of deionized water and stirred to form a solution 1;
[0071] (2) heating solution 1 to 70° C. in a water bath, adding 0.3 g of κ carrageenan and 0.3 g of potassium chloride thereto, and removing bubbles and dissolved gases in the solution by ultrasonication (ultrasonicator, ultrasonic power of 30 W, ultrasonic time of 3 min) to form a hydrogel precursor solution;
[0072] (3) The artificial joint made of PEEK was precooled to -7°C, immersed in the hydrogel precursor solution for 1 second and taken out to form a hydrogel coating with a thickness of 200 μm. The surface was covered with a PTFE film and placed in a UV box for curing (UV wavelength of 365 nm). -1 , UV power is 350mW / cm 2 The UV curing time is 70 minutes), so that the hydrogel precursor solution and PEEK react, cross-link and self-assemble to form a supramolecular hydrogel, thereby obtaining a hydrogel wear-resistant coating for PEEK artificial joints.
[0073] Example 10
[0074] (1) 3 g of acrylamide, 0.1 g of N,N'-methylenebisacrylamide and 0.01 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone were dissolved in 10 ml of deionized water and stirred to form a solution 1;
[0075] (2) heating solution 1 to 80° C. in a water bath, adding 0.15 g of κ carrageenan and 0.1 g of potassium chloride thereto, and removing bubbles and dissolved gases in the solution by ultrasonication (ultrasonicator, ultrasonic power of 30 W, ultrasonic time of 2 min) to form a hydrogel precursor solution;
[0076] (3) The artificial joint made of PEEK was precooled to -10°C, immersed in the hydrogel precursor solution for 1 second and taken out to form a hydrogel coating with a thickness of 200 μm. The surface was covered with a PTFE film and placed in a UV box for curing (UV wavelength of 365 nm). -1 , UV power is 350mW / cm 2 The ultraviolet curing time is 90 minutes), so that the hydrogel precursor solution and PEEK react, cross-link and self-assemble to form a supramolecular hydrogel, thereby obtaining a hydrogel wear-resistant coating for PEEK artificial joints.
[0077] Embodiment 11
[0078] (1) 6 g of acrylamide, 0.01 g of N,N'-methylenebisacrylamide and 0.0005 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone were dissolved in 10 ml of deionized water and stirred to form a solution 1;
[0079] (2) heating solution 1 to 90° C. in a water bath, adding 0.25 g of κ carrageenan and 0.01 g of potassium chloride thereto, and removing bubbles and dissolved gases in the solution by ultrasonication (ultrasonicator, ultrasonic power of 30 W, ultrasonic time of 1 min) to form a hydrogel precursor solution;
[0080] (3) The artificial joint made of PEEK was precooled to -4°C, immersed in the hydrogel precursor solution for 1 second and taken out to form a hydrogel coating with a thickness of 200 μm. The surface was covered with a PTFE film and placed in a UV box for curing (UV wavelength of 365 nm). -1 , UV power is 350mW / cm 2 The ultraviolet curing time is 80 minutes), so that the hydrogel precursor solution and PEEK react, cross-link and self-assemble to form a supramolecular hydrogel, thereby obtaining a hydrogel wear-resistant coating for PEEK artificial joints.
[0081] Example 12
[0082] (1) dissolving 6 g of acrylamide, 0.006 g of N,N'-methylenebisacrylamide and 0.0001 g of ammonium persulfate in 10 ml of deionized water and stirring to form solution 2;
[0083] (2) heating solution 2 to 65° C. in a water bath, adding 0.3 g of κ carrageenan and 0.003 g of potassium chloride thereto, and removing bubbles and dissolved gases in the solution by ultrasonication (ultrasonicator, ultrasonic power of 30 W, ultrasonic time of 2 min) to form a hydrogel precursor solution;
[0084] (3) The PEEK sheet was precooled to -15°C, a hydrogel precursor solution was dripped onto the surface, the surface was covered with a glass sheet and placed in a 70°C water bath for 2 h, so that the hydrogel precursor solution and PEEK reacted to cross-link and self-assemble to form a supramolecular hydrogel, thereby obtaining a hydrogel wear-resistant coating for PEEK artificial joints.
[0085] Example 13
[0086] (1) dissolving 6 g of acrylamide, 0.006 g of N,N'-methylenebisacrylamide and 0.1 g of ammonium persulfate in 10 ml of deionized water and stirring to form solution 2;
[0087] (2) heating solution 2 to 75° C. in a water bath, adding 0.3 g of κ carrageenan and 0.003 g of potassium chloride thereto, and removing bubbles and dissolved gases in the solution by ultrasonication (ultrasonicator, ultrasonic power of 30 W, ultrasonic time of 3 min) to form a hydrogel precursor solution;
[0088] (3) The PEEK sheet was precooled to -10°C, a hydrogel precursor solution was dripped onto the surface, the surface was covered with a glass sheet and placed in an 85°C water bath for 1.5 h to allow the hydrogel precursor solution to react with PEEK to cross-link and self-assemble to form a supramolecular hydrogel, thereby obtaining a hydrogel wear-resistant coating for PEEK artificial joints.
[0089] Embodiment 14
[0090] (1) dissolving 6 g of acrylamide, 0.006 g of N,N'-methylenebisacrylamide and 0.01 g of ammonium persulfate in 10 ml of deionized water and stirring to form solution 2;
[0091] (2) heating solution 2 to 85° C. in a water bath, adding 0.3 g of κ carrageenan and 0.003 g of potassium chloride thereto, and removing bubbles and dissolved gases in the solution by ultrasonication (ultrasonicator, ultrasonic power 30 W, ultrasonic time 0.5 min), to form a hydrogel precursor solution;
[0092] (3) The PEEK sheet was precooled to -4°C, a hydrogel precursor solution was dripped onto the surface, the surface was covered with a glass sheet and placed in a 90°C water bath for 1 h, so that the hydrogel precursor solution and PEEK reacted to cross-link and self-assemble to form a supramolecular hydrogel, thereby obtaining a hydrogel wear-resistant coating for PEEK artificial joints.
[0093] The present invention is not limited to the concentration and number of layers prepared in the embodiments of the present invention. In particular, higher concentrations will have more excellent tribological performance. The present invention is also applicable to PEEK surfaces at non-articular parts of artificial joints.
[0094] Friction and wear properties of the hydrogel wear-resistant coating of the present invention:
[0095] The tribological properties of the substrate PEEK and different coating materials were investigated using a UMT2 friction and wear testing machine. The friction test conditions were: load 1N, frequency 2Hz (speed 24mm / s), and a stainless steel ball with a diameter of 9.5mm. Figure 3 The tribological performance diagram of coating materials with different thicknesses in Examples 1-7 shows that PEEK exhibits an average friction coefficient of 0.3-0.4. After adding the coating, the friction coefficient drops below 0.05. In particular, the thinner the coating, the lower the friction coefficient. Subsequently, the coating with a thickness of 200 μm in Example 1 was used for coating durability testing. Figure 4 (a), (b), (c) and (d) are tribological performance diagrams after 4 hours and 288,000 cycles. The friction coefficient is always lower than 0.06, and the wear is difficult to distinguish with the naked eye. The wear scar is analyzed by laser confocal microscope, and the wear volume is 4.5×10 -5 mm 3 / Nm. This shows that the coating can effectively reduce the friction coefficient and wear rate of PEEK and exhibit good lubrication and wear resistance.
[0096] Biocompatibility of the hydrogel wear-resistant coating of the present invention:
[0097] A PEEK sheet with a diameter of 14 mm and a thickness of 1 mm was prepared, and a hydrogel wear-resistant coating with a thickness of 200 μm for PEEK artificial joints in Example 1 was prepared on the surface. The leaching mixture was placed in a constant temperature box at 37±1°C, and the material was taken out after 24±2 hours to obtain the corresponding leaching solution of each group. The groups were divided into a PEEK group, a PAAm coating group on PEEK, and a KC / PAAM coating group on PEEK. Fibroblasts were inoculated into the leaching solution, and the OD value of each group was observed at different times.
[0098] Figure 5The OD values of Example 1 at 1 day, 3 days and 5 days were shown. After culture, each group showed good biocompatibility, indicating that both PAAm and KC / PAAm coatings had no obvious cytotoxicity, that is, each component of the prepared PEEK surface hydrogel coating had excellent biocompatibility.
[0099] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0100] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing a hydrogel wear-resistant coating for PEEK artificial joints, characterized in that: The following steps are involved: (1) dissolving acrylamide, N,N'-methylenebisacrylamide and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone in deionized water and stirring until dissolved, or dissolving acrylamide, N,N'-methylenebisacrylamide and ammonium persulfate in deionized water and stirring until dissolved; adding kappa carrageenan and potassium chloride under heating and ultrasonication to form a hydrogel precursor solution; (2) Precooling the PEEK and immersing it in a hydrogel precursor solution to form a hydrogel coating, which is then cured to obtain a hydrogel wear-resistant coating for a PEEK artificial joint.
2. The method for preparing a hydrogel wear-resistant coating for a PEEK artificial joint according to claim 1, characterized in that: In the hydrogel precursor solution, the concentration of acrylamide is 100-800 mg / mL, the concentration of N,N'-methylenebisacrylamide is 0.1-20 mg / mL, and the concentration of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone is 0.05-20 mg / mL.
3. The method for preparing a hydrogel wear-resistant coating for a PEEK artificial joint according to claim 1, characterized in that: The concentration of κ carrageenan is 12 to 30 mg / mL, the concentration of potassium chloride is 1.2 to 30 mg / mL, and the concentration of ammonium persulfate is 0.01 to 10 mg / mL.
4. The method for preparing a hydrogel wear-resistant coating for a PEEK artificial joint according to claim 1, characterized in that: The heating temperature is 60-90°C.
5. The method for preparing a hydrogel wear-resistant coating for a PEEK artificial joint according to claim 1, characterized in that: The ultrasonic power is 30W, and the ultrasonic time is 0.5min to 3min.
6. The method for preparing a hydrogel wear-resistant coating for a PEEK artificial joint according to claim 1, characterized in that: The precooling temperature is -18°C to -4°C, and the time for immersing the precooled PEEK in the hydrogel precursor solution is 0.5s to 10s.
7. The method for preparing a hydrogel wear-resistant coating for PEEK artificial joints according to claim 1, characterized in that: The thickness of the hydrogel coating is 200 to 1800 μm.
8. The method for preparing a hydrogel wear-resistant coating for PEEK artificial joints according to claim 1, characterized in that: When the hydrogel precursor solution contains 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, the curing conditions are: at an ultraviolet wavelength of 365nm -1 、UV power is 350mW / cm 2 UV curing for 50min to 90min; When the hydrogel precursor solution contains ammonium persulfate, the curing conditions are: heating at 70 to 90° C. for 60 to 120 minutes.
9. The method for preparing a hydrogel wear-resistant coating for PEEK artificial joints according to claim 1, characterized in that: The following steps are also included: (3) repeating step (1) to obtain a hydrogel precursor solution; (4) adding the hydrogel precursor solution obtained in step (3) dropwise onto the hydrogel wear-resistant coating for PEEK artificial joints prepared in step (2), and curing the solution to obtain a double-layer hydrogel wear-resistant coating for PEEK artificial joints.
10. A hydrogel wear-resistant coating for PEEK artificial joints prepared according to the method according to any one of claims 1 to 9.